Analisis Historis, Metode Dan Karakteristik Pendidikan Tasawuf Di Ma’had Aly IqnᾹ’ Ath-ThᾹlῙbin Pondok Pesantren Al-Anwar, Sarang, Rembang - Mahmudi, Kholis Ali; Gusmian, Islah (Jurnal Keislaman, 2024)
This research aims to examine: (1) the history of the establishment of Ma'had Aly Iqnā' Ath-Thālibīn Pondok Pesantren Al-Anwar, Sarang, Rembang (2) Taṣawuf education at Ma'had Aly Iqnā' Ath-Thālibīn Pondok Pesantren Al-Anwar, Sarang, Rembang (3) the characteristics of Taṣawuf education at Ma'had Aly Iqnā' Ath-Thālibīn Pondok Pesantren Al-Anwar, Sarang, Rembang. The research approach used in this study is descriptive qualitative. The research setting was conducted at Ma'had Aly Iqnā' Ath-Thālibīn Pondok Pesantren Al-Anwar, Sarang, Rembang. The data collection method uses documentation, interview, and observation methods. For data validity techniques used are source triangulation techniques. While the data analysis technique that researchers obtained, using data collection, data reduction, and data verification. The results of the study conclude The learning method follows the tradition of the salaf pesantren and emphasizes social practice. Its characteristics include the use of the book by Masyayikh PP. Al-Anwar, sanadan kitab, syarh kitab as a final assignment, and the application of Sufism in social life.